2014
DOI: 10.1002/2014jd021624
|View full text |Cite
|
Sign up to set email alerts
|

Mapping thunder sources by inverting acoustic and electromagnetic observations

Abstract: We present a new method of locating current flow in lightning strikes by inversion of thunder recordings constrained by Lightning Mapping Array observations. First, radio frequency (RF) pulses are connected to reconstruct conductive channels created by leaders. Then, acoustic signals that would be produced by current flow through each channel are forward modeled. The recorded thunder is considered to consist of a weighted superposition of these acoustic signals. We calculate the posterior distribution of acous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 30 publications
0
15
1
1
Order By: Relevance
“…For the ray propagation and eigenray modeling we have assumed a point source for the lightning infrasound at 4‐km altitude. Infrasound sources from lightning have been mapped up to 12‐km altitude in the thundercloud (J. F. Anderson et al, ; Arechiga et al, ). Furthermore, the mapped current flow within lightning strokes suggests that the source geometry can resemble complex, dendritic structures (J. F. Anderson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…For the ray propagation and eigenray modeling we have assumed a point source for the lightning infrasound at 4‐km altitude. Infrasound sources from lightning have been mapped up to 12‐km altitude in the thundercloud (J. F. Anderson et al, ; Arechiga et al, ). Furthermore, the mapped current flow within lightning strokes suggests that the source geometry can resemble complex, dendritic structures (J. F. Anderson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic Data Teer and Few [1974] 17 CG and 20 IC [Arizona storm, also studied in MacGorman et al 1981] MacGorman et al [1981] statistics on three storms: Arizona (26 + 11 flashes), Colorado (35 flashes), and Florida (9 flashes) Arechiga et al [2011] two triggered lightning flashes Johnson et al [2011] at least 24 natural lightning flashes Qiu et al [2012] two natural lightning flashes Bodhika et al [2013] two natural lightning flashes, no comparison with LMA Arechiga et al [2014] two intracloud natural lightning flashes Anderson et al [2014] eight natural lightning flashes camera . The authors found a good agreement between the acoustic reconstructions and the pictures when the discharge is visible, being outside the storm cloud.…”
Section: Authorsmentioning
confidence: 99%
“…The determination of uncertainties associated to acoustic reconstructions is an active research field: Arechiga et al [2014] and Anderson et al [2014] discussed the impact of meteorological profiles on localization.…”
Section: Authorsmentioning
confidence: 99%
“…These glitches include a one-sample voltage spike preceded and followed by brief oscillations (presumably induced by the data logger's antialiasing filter); they appear on all channels within the same sample interval (0.001 s) with distinct waveforms ( Figure S3). Such characteristics are unlikely for acoustic waves but are typical of glitches observed to coincide with lightning strikes during thunderstorms, which are interpreted as electromagnetic interference from radio waves generated during lightning strikes (Anderson et al, 2014). Volcanic lightning is common in explosive eruptions and forms as a result of charging due to violent interactions between ash particles or, if present, hydrometeors (Behnke et al, 2013;Cimarelli et al, 2014).…”
Section: Electrical Activitymentioning
confidence: 99%